2007
DOI: 10.1007/s00268-006-0135-0
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence after Total Thyroidectomy for Benign Multinodular Goiter

Abstract: Total thyroidectomy for BMNG is not only a safe procedure but is efficacious in preventing recurrent disease. Failure to remove embryological remnants such as thyrothymic residue or pyramidal remnants during total thyroidectomy is the major cause of recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
61
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(66 citation statements)
references
References 42 publications
3
61
0
2
Order By: Relevance
“…6 During the 1980s-1990s there were authors who favored an ST in the treatment of benign diseases due to the proposed lower incidence of surgical complications and supposed postoperative euthyroid state, 7-9 while others advocated the use of a TT because of a similar complication rate to the subtotal procedure and proposed lower pathologic recurrence rate. [10][11][12] Our previous study on the subject also supports the TT choice.…”
Section: Discussionmentioning
confidence: 99%
“…6 During the 1980s-1990s there were authors who favored an ST in the treatment of benign diseases due to the proposed lower incidence of surgical complications and supposed postoperative euthyroid state, 7-9 while others advocated the use of a TT because of a similar complication rate to the subtotal procedure and proposed lower pathologic recurrence rate. [10][11][12] Our previous study on the subject also supports the TT choice.…”
Section: Discussionmentioning
confidence: 99%
“…Total thyroidectomy is the operation of choice for multinodular goiter for the majority of endocrine surgeons (Hisham et al 2001, Snook et al 2007). Thus, total thyroidectomy is recommended for a suspicious nodule in multinodular goiter.…”
Section: Discussionmentioning
confidence: 99%
“…Vaiman et al described a recurrence rate of over 20% for benign thyroid diseases after subtotal thyroidectomy [23]. Other studies, too, have demonstrated that total thyroidectomy for multinodular goitre is a safe as well as an effective procedure in preventing goitre recurrence [24,25] and, due to a higher rate of complications after surgery for recurrent goitre, total thyroidectomy for multinodular goitre is advisable [26].…”
Section: Discussionmentioning
confidence: 95%